Comprehensive Review of Available Nanotechnological Techniques for Treating Nonsolid Tumors - Astha Shekhar; Sarita Singh; Kriti Gupta; Ambak K. Rai; Ravi Prakash Tewari (Nano Biomedicine and Engineering, 2023)
Nanotechnology has become integral in the improvement of methodology used to identify and treat various cancers. Nanoparticles (NPs) exhibit unique features that enhance sensitivity and selectivity and subsequently reduce the time required to detect early-stage cancer through biomarkers. NPs improve the therapeutic efficiency of anticancer agents when compared with conventional methods, such as chemotherapy, and thereby eliminate toxicity and side effects, which helps improve the stability, solubility, half-life, and tumor aggregation of an anticancer drug. This also helps expedite the treatment cycle by enabling a real-time assessment, quickly circumventing various biological barriers, improving vectorization and delivery, overcoming drug resistance, and developing various paths for the manufacturing of new synthetic vaccines. Nanomedicine has usually involved studies on solid-state cancers because it can increase the cell permeability and retention effect experienced within the tumor areas to improve regional accumulation and efficacy. Nanomedicine for leukemia and lymphoma is addressed differently from solid-state cancers because of the absence of the enhanced permeability and retention effect. Nevertheless, nanomedicine has enabled the development of various modern innovative techniques for simple and noninvasive procedures for prior analysis of cancers with subsequent diffuse tumor treatment. In this assessment, we consider various unique constructs on NPs that can predominantly enhance therapeutic treatment over diffused tumors by increasing control, from preclinical testing to medicinal trials. Nanotechnology combines nanodiagnostics, nanotherapeutics, and nanotheranostics for improved imaging and diagnoses of early stage cancers. Furthermore, the primacy of nanoplatforms has been discussed for an invaluable position in this blended method. There are many types of NPs, such as organic, inorganic, and hybrid NPs. The minute size of NPs makes them ideal for intracellular uptake, and the large surface area ratio allows functional interactions with various compounds. This review also covers targeting cancerous cells via inducing lysosomal autophagy using gold NPs.